(untitled) (Environment & Health, 2017)
Objective: We analyzed the level of the population morbidity in the Rivne region on the basis of integral indicators. Materials and methods: The data, selected for the analysis, show the level of general morbidity of children (0-17 years) and adult (18 and older) population based in terms of 1000 residents of 16 districts in the Rivne region for 2012. Assessment of the morbidity of children and adult population was carried out by the following methods: method of "percentile-profile", method taking into account the age coefficients, method of total placing. Results: The applied methods of the calculation of integral indicators allowed children and adult population morbidity of the Rivne region to be analyzed from different points of view. By the results of the "percentile-profile" method it was possible to divide the areas into two groups - with a level of general morbidity below and above the average level. Method using the age coefficients of morbidity allowed the proportions of adult and children morbidity to be determined in a whole in the Rivne region. The method of total placing allowed the areas with the highest and lowest levels of general morbidity in children and adults to be determined. Conclusions: By the age groups the levels of morbidity in the areas were distributed almost equally, except Radyvylivskyi (it was below the average level in the children’s group and - above in the adult one) and Mlynivskyi areas (in the adult group - below the average level, in the children one - above). They make up 59% and 41% for children and adult population respectively. The lowest level of general morbidity was observed in Dubenskyi area in both age groups and the highest - in Sarnenskyi in both age groups as well. Taking into account obtained results these methods may be applied for the all-round assessment of the indices of the population morbidity and by the separate nosologies.